Problematika Pembelajaran Maharah Kalam Pada Program Pengembangan Bahasa Asing Pondok Pesantren Ngalah Purwosari - Karomatul Jannah (CV. Satria Jaya, 2023)
The mastery of Arabic in Indonesia can be said to be weak, due to the lack of effort and learning of the Arabic language itself. To improve the mastery of Arabic in Dormitory I there is a Foreign Language Development Program (PPBA) which aims to deepen the foreign language of students. In their learning, PPBA students are faced with several problems that can hinder the development of their speaking skills. The aims of this study were: 1) To find out the learning process of speaking skill in PPBA, especially Arabic in Dormitory I. 2) To find out what problems were experienced so that it hindered the speaking skills of Arabic members of Dormitory I. The approach used by the researchers in this study was a qualitative approach. The types of research used are library research and field studies. While the research instruments used for data mining are observation, interviews, and documentation. The research results obtained are: 1) The learning methods used in PPBA Dormitory I are the hiwar method, question and answer with mentors and there is a language day. 2) The problems experienced when learning speaking skills are from the linguistic factor, namely vocabulary mastery, while from non-linguistic factors, namely the language environment, motivation and interest in learning, and the lack of mentor supervision during language days.